Leadership by the Spirit in Pentecostalism: - M.S. Kgatle (Acta Theologica)
Pneumatology refers to the study of the Spirit within Pentecostal theology. Similarly, Pentecostals believe that pneumatology has a role to play in ecclesiastical leadership, which results in leadership through the Holy Spirit. In this article, this kind of leadership is theorised as pneumatocracy and is discussed in contrast to other leadership theories such as autocracy and democracy. The article seeks to demonstrate that pneumatocracy in the Pentecostal movement is important. However, it should engage in societal transformation, development of communities, and socio-economic and -political challenges for its relevance in the 21st century. Furthermore, this theory is proposed as an approach relevant to addressing gender parities in ecclesiastical leadership. The practices of pneumatocracy in early Pentecostalism, the early church, and contemporary times are explored in detail. A transformational pneumatocracy is proposed to address current leadership challenges in the African context.